2004
DOI: 10.1038/sj.mp.4001555
|View full text |Cite
|
Sign up to set email alerts
|

Mental and physical distress is modulated by a polymorphism in the 5-HT transporter gene interacting with social stressors and chronic disease burden

Abstract: Previous studies have yielded conflicting results as to the putative role of the functional polymorphism of the promoter region of the serotonin transporter gene (SLC6A4) in the etiology of anxiety-related traits and depressive disorders. Recently, a significant geneenvironment interaction was found between life stressors, the short allele of the SLC6A4 polymorphism and depression. The aim of the present study was to investigate if such a geneenvironment interaction could be replicated within a different popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
176
7
4

Year Published

2005
2005
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 257 publications
(201 citation statements)
references
References 24 publications
(22 reference statements)
11
176
7
4
Order By: Relevance
“…Even in a study where positive results were reported separately for both genders, the G Â E was stronger in females. 15 Of the four studies with predominantly middle-aged to elderly samples, two showed no evidence of interaction with the non-significant interaction signs pointing in the opposite direction; 44,45 one identified an interaction in the expected direction for female participants only, 41 and one in the whole sample after correcting for gender. 32 The observed pattern of variation by age and gender is likely to reflect several interacting factors.…”
Section: Methodsmentioning
confidence: 94%
See 4 more Smart Citations
“…Even in a study where positive results were reported separately for both genders, the G Â E was stronger in females. 15 Of the four studies with predominantly middle-aged to elderly samples, two showed no evidence of interaction with the non-significant interaction signs pointing in the opposite direction; 44,45 one identified an interaction in the expected direction for female participants only, 41 and one in the whole sample after correcting for gender. 32 The observed pattern of variation by age and gender is likely to reflect several interacting factors.…”
Section: Methodsmentioning
confidence: 94%
“…48 Six studies were cross-sectional surveys. 30,31,34,37,39,41,45 One study used a combined cohort/case-control design, selecting participants with extreme scores on either environmental adversity or depression for genotyping. 40 One study examined individuals exposed to a major stressor (myocardial infarction).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations